About difficulties in the examination of the quality of medical care in the complicated course of the postoperative period after cystectomy - K. N. Movchan; K. E. Chernov; B. S. Artyushin; A. V. Zharkov; A. Yu. Chernova (Исследования и практика в медицине)
Cystectomy, as a type of surgical treatment, is performed for various diseases of the bladder. Most often — with malignant tumors, as well as with benign pathological conditions. Complications in the postoperative period in patients undergoing cystectomy are mainly caused by the need to ensure adequate urine derivation. One of the options for solving this problem is the implementation of ileocystoplasty, which, in turn, is associated with the performance of technically difficult and large-scale manipulations during the operation. Successful prevention of severe complications of cystectomy (or their elimination) is probably possible only in those multidisciplinary medical organizations in which the provision of medical care to patients with urological oncology is a daily programmed activity. Outpatient health care specialists play a special role in routing patients with bladder diseases, and not only their formal referral and delivery to multidisciplinary medical and prophylactic institutions in an emergency mode with “on-duty” syndromic diagnoses such as “renal colic or hematuria”. At present, in St. Petersburg, all conditions have been created for the concentration of patients with severe diseases of the bladder in a number of specialized medical organizations, in which a large number of cystectomies with intestinal plastic are routinely performed annually, which makes it possible with a high probability to guarantee a favorable clinical outcome without discrediting method of the rarity of its implementation.